RNA activation‐independent DNA targeting of the Type III CRISPR‐Cas system by a Csm complex. (31st March 2017) - Park, Kwang‐Hyun; An, Yan; Jung, Tae‐Yang; Baek, In‐Young; Noh, Haemin; Ahn, Woo‐Chan; Hebert, Hans; Song, Ji‐Joon; Kim, Jeong‐Hoon; Oh, Byung‐Ha; Woo, Eui‐Jeon
Abstract: The CRISPR‐Cas system is an adaptive and heritable immune response that destroys invading foreign nucleic acids. The effector complex of the Type III CRISPR‐Cas system targets RNA and DNA in a transcription‐coupled manner, but the exact mechanism of DNA targeting by this complex remains elusive. In this study, an effector Csm holocomplex derived from Thermococcus onnurineus is reconstituted with a minimalistic combination of Csm11 21 33 41 51, and shows RNA targeting and RNA‐activated single‐stranded DNA (ssDNA) targeting activities. Unexpectedly, in the absence of an RNA transcript, it cleaves ssDNA containing a sequence complementary to the bound crRNA guide region in a manner dependent on the HD domain of the Csm1 subunit. This nuclease activity is blocked by a repeat tag found in the host CRISPR loci. The specific cleavage of ssDNA without a target RNA suggests a novel ssDNA targeting mechanism of the Type III system, which could facilitate the efficient and complete degradation of foreign nucleic acids. Synopsis: The Type III CRISPR‐Cas system in T. onnurineus cleaves target ssDNA in a direct cis ‐acting and target RNA‐independent manner, suggesting a novel ssDNA targeting mechanism of the Type III system. The Csm effector complex of T. onnurineus was reconstituted with a minimalistic combination of Csm11 21 33 41 51 . The complex shows RNA targeting and RNA‐activated ssDNA targeting activities. The complex shows RNA activation‐independent ssDNA targeting activity that requires the HD domain of the Csm1 subunit. Abstract : The Type III CRISPR‐Cas system in T. onnurineus cleaves target ssDNA in a direct cis ‐acting and target RNA‐independent manner, suggesting a novel ssDNA targeting mechanism of the Type III system.